Improving the rheological and stability characteristics of highly concentrated aqueous yttria stabilized zirconia slurries. Issue 17 (1st December 2020) - Yaghtin, Maryam; Yaghtin, Amirhossein; Tang, Zhaolin; Troczynski, Tom
Abstract: Highly concentrated yttria stabilized zirconia (YSZ) aqueous suspensions with improved rheology and stability characteristics are desired in several fields of modern ceramic engineering such as Suspension Plasma Sprayed (SPS) coatings. In this study, water-based suspensions of YSZ with 30 wt% solid loading were selected to investigate the effect of pH, dispersant type and its concentration on the dispersion and rheological properties of the suspensions. Polyethyleneimine solution (PEI), 2-phosphonobutane-1, 2, 4-tricarboxylic acid (PBTCA) and alpha-Terpineol ( α -Terpineol) were used as dispersant agents. Careful investigations of the suspensions were conducted through viscosity, zeta potential, turbidity, destabilization kinetics, and sedimentation rate measurements. The results showed that dispersant addition, when combined with proper pH adjustment, can significantly decrease the suspensions' viscosity values and improve their stabilities. Optimum viscosity and stability conditions, defined as viscosities lower than 4 cp and Nephelometric turbidity units (NTU) higher than 3000 were obtained with 0.1 wt% PEI addition at pH value of 2.5, 0.05 wt% PBTCA at pH value of 10.5 and 0.1 wt% α -Terpineol at pH value of 2.5.